Child feeding practices and its predictors among the mothers/primary care providers of 6–36-month-old children: A community-based analytical study in a town of eastern India - Rajib Saha; Sumanta Chakraborty (MRIMS Journal of Health Sciences, 2025)
Background: Suboptimal and neglected young child feeding practice compromises their growth as well as nutrition. Objective: The study was conducted to find out the predictors of good child-feeding practices among the mothers/primary care providers. Methodology: This community-based analytical cross-sectional epidemiological study was conducted between September 2022 and December 2022 among 216 mothers or primary care providers of 6–36-month-old children in Bankura municipality area, West Bengal, using predesigned and pretested questionnaire a part of infant young and child feeding-child care provider questionnaire. Factors which were found statistically significant in bivariate analysis were considered for multivariable linear regression. Results: With the increasing of birth order one, being part of the nuclear family, and increasing of 1 month of child’s age, overall child feeding practice score was found 1.905, 4.920, and 0.183 times better than others, respectively, within 15–60 score range. Mothers who never seek care from any health-care system were found 2.331 higher handling and cleaning of milk bottle practice score than others and with increasing of 1 month of the child’s age, preparing, handling, and storing food practice score increased 0.61 within 5–20 score range. In case of a male child and with increasing of 1 month of the child’s age, responsive feeding score increased 1.924 and 0.81 times, respectively, within 5–20 score range. Conclusion: Experience and time improved the feeding practice of the caregivers. Feeding practice-related counseling should be integrated priority basis with the child’s follow-up visit.